O Documento Curricular do Território Maranhense (DCTMA) e suas implicações para o ensino de História nos anos iniciais – uma análise a partir da perspectiva intercultural - SILVA, Mariana Matos (2023)
In contemporary times, talking about curriculum includes accessing different cultural, social, and political spheres of a territory and its people. In this sense, a democratic curriculum would be the one that is aware of cultures, differences, and diversities, and considers local specificities, even under the guidelines of policies and curriculum documents. The present study has the Curriculum Document of the Maranhão Territory (DCTMA) as research object, focusing on the analysis and problematization of the curricular component History, from the initial years of Elementary School. The documentary research, qualitative in nature, considers especially the so-called "Thematic Units" of this curricular component in an attempt to identify to what extent and in which way an education in the light of the intercultural perspective is possible. In general, considering the proposals present in the "Thematic Units" under analysis, the DCTMA denotes a constant contrast in the proposals of the objects of knowledge and their abilities. It is possible to identify in the curricular organizer of the History curriculum component attempts to work on other knowledge, but, on the other hand, it also minimizes the possibilities of problematization of the themes by intercultural education. The reflections developed were the basis for the creation of a website directed especially to the teaching public. In it, some intercultural didactic suggestions for the teaching of History are gathered. The platform, besides the curricular recommendations, offers a forum environment for the dialogue and exchange of experiences among teachers in search of the "interculturalizing" in the curriculum. The proposal as the site is to enable a pedagogical practice capable of creating connections between interculturality, DCTMA and teachers as a way to investigate with interculturality the vicissitudes of the curriculum in their daily lives.